2016
DOI: 10.1007/s00436-016-4917-5
|View full text |Cite
|
Sign up to set email alerts
|

Detection by PCR of pathogenic protozoa in raw and drinkable water samples in Colombia

Abstract: We evaluated the presence of DNA of Giardia, Toxoplasma, and Cryptosporidium by PCR, and of Giardia and Cryptosporidium genera by immunofluorescence antibody test (IFAT), in water samples, before, during, and after plant treatment for drinkable water. We applied this method in 38 samples of 10 l of water taken from each of the water treatment steps and in 8 samples taken at home (only for Toxoplasma PCR) in Quindio region in Colombia. There were 8 positive samples for Cryptosporidium parvum (21 %), 4 for Crypt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 24 publications
4
33
0
9
Order By: Relevance
“…Sequencing of PCR results was also important to discriminate between species for Cryptosporidium and in the present work it was possible to identify C. hominis in stools from children and to detect C. parvum in water and surface. We have reported that C. parvum is detected in tap water more frequently than C. hominis in our city (Triviño‐Valencia et al, ).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Sequencing of PCR results was also important to discriminate between species for Cryptosporidium and in the present work it was possible to identify C. hominis in stools from children and to detect C. parvum in water and surface. We have reported that C. parvum is detected in tap water more frequently than C. hominis in our city (Triviño‐Valencia et al, ).…”
Section: Discussionmentioning
confidence: 60%
“…For food, live, and surface samples, the DNeasy Blood & Tissue Extraction Kit (Qiagen, Germany) with mechanical lysis and zirconium beads were applied five times for DNA extraction after agitation in a stomacher 400‐W BagMixer (Interscience, France) at 260 rpm for 30 s with glycine 1 M (Biorad, Estados Unidos) and pH of 5.5 and a wash solution (PBS 1X, 100 μl of Tween 80, Merck, Germany, and 10 g of sulfamic acid—Merck, Germany) at pH of 7.5, respectively (Cook et al, ), and a formalin–ether concentration method for water eluates was applied (also for inert and live surface samples), as described (Hernández‐Arango, Pinto, Muñoz‐Sanchez, Lora‐Suarez, & Gómez‐Marín, ; Lora‐Suarez, Rivera, Triviño‐Valencia, & Gomez‐Marin, ; Triviño‐Valencia, Lora, Zuluaga, & Gomez‐Marin, ). For stools, 1 g of sample was diluted in 5 ml of sterile saline solution at 0.9% and filtered through gauze.…”
Section: Methodsmentioning
confidence: 99%
“…The supernatant was discarded and 600 lL of DNAzol (Invitrogen, USA), 10 lL of isoamyl alcohol (Fisher Scientific, USA) and 0.3 g of zirconium silicate beads with 0.5 mm diameter (BioSpec, USA) were added. Afterwards, the tubes were shaken five times in a Mini Bead Beater (BioSpec, USA) to maximum speed for 1 minute and 1 minute in ice [41]. Later, a Wizard Genomic DNA extraction kit (Promega, USA) was used for nuclear lysis and purification, following the manufacturer's protocol.…”
Section: Toxoplasma Gondii Dna Extraction Procedures and Pcr Detectionmentioning
confidence: 99%
“…To date, this parasitic occurrence has been reported in different geographical location of river [5]. In fact, 11.5% of Malaysian river water samples were reported to get contaminated with Cryptosporidium oocysts [6]. Recently, two cases have been reported on Cryptosporidium occurrence in Kuantan, Pahang [7,8].…”
Section: Introductionmentioning
confidence: 99%